Tracking the Stratosphere‐to‐Surface Impact of Sudden Stratospheric Warmings. Issue 3 (4th February 2021) - Hall, Richard J.; Mitchell, Daniel M.; Seviour, William J. M.; Wright, Corwin J.
Abstract: Sudden stratospheric warming (SSW) events are extreme atmospheric regimes which can have a signature in surface weather up to 40 days after event onset in the stratosphere. SSWs can be classified as either vortex splitting or vortex displacement events, with the nature and timing of the surface impact potentially being different between the two. In this study, using ERA40/Interim reanalysis data, we develop a simple empirical downward tracking algorithm which for the first time allows us to estimate the time of surface impact for individual SSW events. We show that the surface impact following splitting events is, on average, about 1 week earlier than following displacement events, albeit with considerable variability. By compositing tropospheric responses around the identified date of surface impact, rather than around the central stratospheric onset date as common in previous studies, we can better constrain the surface signal of SSWs. We find that while the difference in North Atlantic Oscillation anomalies between split and displacement vortices is small, surface temperature anomalies over northwest Europe and northern Eurasia are significantly colder for splitting events, particularly over the UK just prior to the surface impact date. Displacement events on average are wetter over Northwest Europe around the time of surface impact, consistent with the jet stream being displaced further south in response to split events. Our downtracking algorithm can be used with any reanalyzes and gridded model data, and therefore will be a valuable tool for use with the latest climate models. Key Points: We develop a tracking algorithm to estimate the date of surface impact of sudden stratospheric warmings (SSWs) The method enables separation of the timings and magnitudes of surface impacts of displacement and split SSWs The method will be a valuable tool for use with climate models